Advances in Grape and Wine Biotechnology - Morata, Antonio; Loira, Iris (IntechOpen, 2019)
Advances in Grape and Wine Biotechnology is a collection of fifteen chapters that addresses different issues related to the technological and biotechnological management of vineyards and winemaking. It focuses on recent advances in the field of viticulture with interesting topics such as the development of a microvine model for research purposes, the mechanisms of cultivar adaptation and evolution in a climate change scenario, and the consequences of vine water deficit on yield components. Other topics include the metabolic profiling of different Saccharomyces and non-Saccharomyces yeast species and their contribution in modulating the sensory quality of wines produced in warm regions, the use of new natural and sustainable fining agents, and available physical methods to reduce alcohol content. This volume will be of great interest to researchers and vine or wine professionals. MENTION SPÉCIALE DE L'OIV 2020 OIV SPECIAL MENTION